Analysis of Shoreline Changes Period 1991 – 2001 Pasumpahan Island, Padang, West Sumatera - Sanora, Fifi; Rifaldi, Rifaldi; Elizal, Elizal (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Pasumpahan Island is an area that is affected by currents, waves and sedimentation processes because it is directly adjacent to the Indian Ocean and the mouth of the Pisang River, this causes changes in the coastline in the form of abrasion and accretion on the island. This study aims to determine the effect of currents, waves, and sedimentation processes on the rate of change of the shoreline for 10 years (1991-2001) on Pasumpahan Island. This research was conducted in March 2022 on Pasumpahan Island, Padang City, West Sumatra Province. The method used is a survey method to obtain primary data including current speed, heightwaves and sediments. The study method used is a quantitative method with a multi-temporal satellite imagery approachusing the Digital Shoreline Analysis System (DSAS) software with the End Point Rate (EPR) approach. The results of the analysis of current velocity values ​​ranged from 0.21-0.28 m/s, wave heights ranged from 0.24-0.55 m, the average diameter of the sediment ranged from 0.83-1 Φ. The results of image data processing show that there has been a change in the shoreline in the form of low category abrasion (0.4 m/year), stable (1.42 m/year), and accretion (3.07 m/year) on Pasumpahan Island.